2018
DOI: 10.1177/0363546518776978
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Glenoid Bone Defect in Anterior Shoulder Instability: Latarjet Procedure Versus Bankart Repair

Abstract: The Latarjet procedure and arthroscopic Bankart repair both provided satisfactory clinical outcome scores and pain relief for anterior shoulder instability with a borderline glenoid bone defect. However, the Latarjet procedure resulted in significantly lower recurrences and less external rotation limitation than the arthroscopic Bankart repair. Therefore, the Latarjet procedure could be a more reliable surgical option in anterior recurrent instability with a borderline glenoid bone defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 34 publications
2
49
0
3
Order By: Relevance
“…Thank you for citing the studies regarding no difference in outcome between arthroscopic Bankart and open Latarjet in terms of rate of RTS. 5,6,18,30 Depending on how the data are interpreted, our study does not disagree with these results. We showed that of the athletes who were able to RTS, 91.5% of those receiving arthroscopic Bankart and 90% of those receiving open Latarjet returned to preinjury levels (Table 6), which is not significantly different.…”
supporting
confidence: 46%
“…Thank you for citing the studies regarding no difference in outcome between arthroscopic Bankart and open Latarjet in terms of rate of RTS. 5,6,18,30 Depending on how the data are interpreted, our study does not disagree with these results. We showed that of the athletes who were able to RTS, 91.5% of those receiving arthroscopic Bankart and 90% of those receiving open Latarjet returned to preinjury levels (Table 6), which is not significantly different.…”
supporting
confidence: 46%
“…11 Several studies have defined subcritical glenoid bone loss and examined the impact of outcomes after isolated labral repair in patients with subcritical bone loss. 10,15,19 Shaha and colleagues 24 reported that 13.5% glenoid bone loss was associated with poor outcomes in patients who underwent isolated arthroscopic labral repair. They measured bone loss using magnetic resonance imaging with the perfect circle technique described by Harmsen and Huijsmans, 13 and patients were divided into quartiles based on the percentage of bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…38 Although a 2018 systematic review by Adam et al 2 reported an average recurrence rate of 13.7% after arthroscopic Bankart repair and a revision rate of 7.1%, rates of recurrence are highly variable, with reported rates ranging from 2% 25,28,34 to 40%. 31,84…”
mentioning
confidence: 99%